Industrial Agroforestry: An Indian Tobacco Company (ITC) initiative - Kulkarni, H.D. (Indian Journal of Agroforestry, 2020)
World-over the common practice for growing pulpwood plantation is to plant with a single species in a large and continuous block on a forest area which was acquired, clear felled and planted. ITCâ€™s pulpwood plantations differ as they are grown on private lands with agricultural crops which are small and discrete plots. The productivity of pulpwood clonal plantations under agroforestry recorded is 20 to 58 t/ha/yr compared to 6 to10 t/ha/yr from seed origin plantations. ITC has successfully promoted 158,000 ha plantations in the last 21 years. To start with block plantations were raised with a spacing of 3 x 1.5 m with 2222 trees / ha facilitating intercropping in between the lines in the first year. Later, the new planting pattern was evolved after a series of experiments with different planting geometry. Trees are planted apart either in a single or double row (Alley cropping) leaving a wide gap of 8 m for growing crops in all the 4 years of plantation cycle. The land allocated was 25% for tree crops and 75% for agricultural crops enabling the farmer to take food crops every year regularly and harvest the trees after 4 years. This model accommodate 2000 trees / ha and the yields remained the same. In case of agricultural crop losses due to drought, flood, pest and diseases, the income from tree hedge the risks. The novelty of the agroforestry model is to improve the farm productivity and profitability while conserving the environment and bringing diversification on farm lands. ITC has put up â€œagroforestry for wood and food securityâ€ demo plots in Andhra Pradesh and Madhya Pradesh over an area of 6500 ha.